Psychosocial effects of surgery and physical activity in bariatric patients: a systematic review - Alejandro Jiménez Loaisa; Vicente Javier Beltrán Carrillo; David González Cutre; Eduardo Cervelló Gimeno (Asociación Española de Ciencias del Deporte, 2015)
Obesity has become one of the major health problems in current industrialized societies. The negative impact of morbid obesity (defined as having a Body Mass Index>40 kg/m2) in the health-related quality of life of patients is significant. Bariatric surgery is currently considered an effective treatment to achieve sustained weight loss in patients with severe obesity, after failure of non-invasive treatments. The role of physical activity for optimizing bariatric surgery outcomes is receiving growing attention. In this sense, the aim of this article was to review the scientific literature concerning the psychosocial effects of surgery and physical activity in bariatric patients. The search was performed using Medline and Scopus databases. From a total of 58 articles, 37 articles were included in the review after the application of exclusion and inclusion criteria. In view of the evidence collected in this review, this article finishes with several conclusions and recommendations linking current knowledge with future research and future health-care interventions with this population.